Multi-Omics Signatures of Oxidative Stress and Inflammation Induced by Short-Term Environmental Particle Gamma Radiation Exposure in Chronic Respiratory Diseases - Sawyer Lehtonen; Deepeak Riao (International Journal of Clinical and Translational Medicine, 2026)
The intersection of environmental particle gamma radiation exposure and chronic respiratory disease has emerged as a critical frontier in systems medicine, demanding integrative analytical frameworks capable of resolving complex molecular cascades. Short-term elevation of gamma-emitting radionuclides attached to inhalable particulate matter triggers rapid oxidative stress and systemic inflammation, disproportionately exacerbating conditions such as chronic obstructive pulmonary disease and asthma. This paper presents a large-scale infrastructure perspective on capturing multi-omics signatures—spanning genomics, epigenomics, transcriptomics, proteomics, and metabolomics—that characterize these acute exposure-response dynamics. We articulate a federated data ecosystem architecture that harmonizes high-resolution environmental radiation monitoring with multi-omics profiling deployed across population cohorts. The design confronts fundamental trade-offs between sensor network granularity, biosample temporal resolution, computational scalability, and representation fairness. We examine how such a platform transforms short-term particle gamma activity measurements into actionable signatures through robust AI-driven pattern extraction, while addressing challenges of batch effects, missing modalities, and algorithmic bias that can distort clinical interpretability across diverse subgroups. Governance models grounded in the FAIR principles and federated learning protect participant privacy and data sovereignty, yet raise questions about accountability, consent, and equitable benefit distribution. By situating the omics signatures within a socio-technical infrastructure, the analysis extends to policy instruments that could regulate ambient particle radioactivity, allocate monitoring resources in environmental justice communities, and embed sustainability into longitudinal exposome initiatives. The resulting framework not only illuminates the oxidative and inflammatory pathways linking short-lived radiation exposure to chronic airway damage but also demonstrates how scalable, fair, and resilient system architectures can translate molecular insights into preventive health strategies.